Poly-l-lactic acid microspheres delay aging of epidermal stem cells in rat skin - Dong, Yunxian; Zhang, Youliang; Yu, Hao; Zhou, Lingcong; Zhang, Yaan; Wang, Haibin; Hu, Zhicheng; Luo, Shengkang (Frontiers in Immunology, 2024)
Objective Injectable skin fillers offer a wider range of options for cutaneous anti-aging and facial rejuvenation. PLLA microspheres are increasingly favored as degradable and long-lasting fillers. The present study focused solely on the effect of PLLA on dermal collagen, without investigating its impact on the epidermis. In this study, we investigated the effects of PLLA microspheres on epidermal stem cells (EpiSCs). Methods Different concentrations of PLLA microspheres on epidermal stem cells (EpiSCs) in vitro through culture, and identification of primary rat EpiSCs. CCK-8 detection, apoptosis staining, flow cytometry, Transwell assay, wound healing assay, q-PCR analysis, and immunofluorescence staining were used to detect the effects of PLLA on EpiSCs. Furthermore, we observed the effect on the epidermis by injecting PLLA into the dermis of the rat skin in vivo. Results PLLA microspheres promote cell proliferation and migration while delaying cell senescence and maintaining its stemness. In vitro, Intradermal injection of PLLA microspheres in the rat back skin resulted in delayed aging, as evidenced by histological and immunohistochemical staining of the skin at 2, 4, and 12 weeks of follow-up. Conclusion This study showed the positive effects of PLLA on rat epidermis and EpiSCs, while providing novel insights into the anti-aging mechanism of PLLA.